Integrando saberes na formação e ação docente: uma proposta metodológica para o ensino de reações químicas em laboratório - Lopes, Cristiane Vieira Nunes Barbosa (2013)
This paper presents a methodological proposal for the teaching of chemical reactions in the laboratory, describing the results of a qualitative study with high school teachers on the applicability of this proposal at a state technical school in Rio de Janeiro. As a product of this dissertation was made a teaching guide, containing two scripts for practice, teaching procedures, materials list, safety guidelines and suggestions for contextualization and conducting classes. Through an alternative approach, we sought to streamline the teaching of chemical reactions, exploring other contents of the curriculum such as thermochemical and solutions. It also sought to promote fusion between the conceptual aspects and action in the laboratory by challenging teachers to think experimental activity not as an isolated moment of the classroom, but as an integral part of it. The methodology was based on a qualitative exploratory approach. Were used as instruments to collect data semi-structured interviews and questionnaires. The research was conducted with chemistry teachers and students of the second year of high school at a state technical school in Rio de Janeiro. The results showed that: i) the initial training of teachers influences the pedagogical approach adopted in conducting practical classes in the laboratory ii) teachers of chemistry, despite initial resistance, accepted the new proposal and contributed to their improvement; iii) through a different proposal, it was possible to integrate theoretical and practical knowledge, the teaching of chemistry in the laboratory, even with time constraints and infrastructure, iv) the scripts submitted promote a dialogic approach to knowledge, valuing the role of the teacher as a mediator of learning; v) the records of the observations of the students, when performed during the practical session - whether in class or in the lab - favor learning vi) more important than the complexity of the proposed experiment, was the relationship of the student with the observed phenomenon, vii ) the approach of content through the experiment allows a more flexible curriculum structure, streamlining the construction of knowledge about chemical reactions. It was concluded that the developed methodological proposal appears as a viable alternative for the promotion of laboratory classes in schools, easing the shortage of textbooks and supporting teachers in the integration of knowledge in chemistry classes.